Uganda : teaching of Swahili : : Education - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Colonial Office file relating to the decision to teach Swahili in Ugandan schools, notably the schools of the Church Missionary Society, as a means of promoting its use as a lingua franca